O triângulo de pascal e a meritocracia: uma sequência didática com o uso do tabuleiro de galton - Lira, Diego de Freitas (2021)
This dissertation presents an association of mathematical content with meritocracy and use of Galton's Board, which are not subjects covered in the high school curriculum, this idea arose from the need to use this mathematical content to discuss a subject that would be done by a teacher from the Humanities area. The objective of this work is to propose a didactic sequence for teaching probability and Combinatorial Analysis, more specifically the study of the Pascal triangle and its properties, using the Galton Board. With these contents to make an association with Meritocracy. To emphasize the use of concrete material and digital technologies, we will use The Common National Curriculum Base (BNCC), presented in 2017 in its final version by the Ministry of Education (MEC) of Brazil. Thus, develop some skills proposed for the area of Mathematics and its Technologies, in order to seek the construction of learning in the classroom. The didactic sequence is supported by Gérard Vergnaud's pedagogical approach, the Theory of Conceptual Fields. The research methodology used is focused on the content and production of educational material. The target audience of this didactic sequence consisted of 2nd year high school students. The proposal is based on numerical tests and subsequent observation of the theoretical probability distribution. Covering this study a little more and using a simulator of the Galton Board made in Geogebra, we will observe the approximation of the histogram of the distribution of the balls in the columns with the Gaussian curve, associating it with meritocracy